High occurrence of antibiotic resistance genes in intensive aquaculture of hybrid snakehead fish - Xiaojing Lin; Xiaojing Lin; Aiping Tan; Yuting Deng; Yuting Deng; Wenwen Liu; Wenwen Liu; Fei Zhao; Zhibin Huang (Frontiers in Marine Science, 2023)
The increasing abundance of antibiotic resistance genes (ARGs), which are regarded as new pollutants, has raised public health concern. The use of antibiotics in aquaculture has promoted the evolution and spread of ARGs. The occurrence and abundance of ARGs in aquaculture has attracted extensive attention. However, the distribution and transmission of ARGs in aquaculture require further study. This study analyzed water and sediment from intensive culture of hybrid snakehead fish farm in Zhongshan, South China. Twenty-two types of ARGs were detected in all environmental samples. The relative abundance of sulfonamide resistance genes (sul1 and sul2) was the highest, ranging from 3.37×10-2 to 8.53×100 copies/16S rRNA gene. High occurrence of quinolones, phenicols, tetracycline resistance genes, and class 1 integrase gene (intI1) was also observed in pond water samples. This implies that pond water is one of the main reservoirs and origins of ARGs in the aquatic environment. Proteobacteria was the most abundant phylum in all the environmental samples, and its relative abundance ranged from 24.05% to 41.84%. Network and canonical correspondence analyses showed that a high abundance of ARGs (int1, sul1, sul2, qacEΔ1, aac6, and oqxA) was positively correlated with Proteobacteria, Cyanobacteria, and Bacteroidetes, and the abundance of Proteobacteria, Actinobacteria, and Patescibacteria was positively correlated with environmental factors (sulfide, nitrite nitrogen, pH, free chlorine, and ammonia nitrogen). These findings demonstrate the prevalence and persistence of ARGs in intensive fish farming in southern China. This suggests that ARG levels and microbiological community composition in aquaculture should be conventionally determined to assess potential risks to public health.